Pengaruh Current Ratio dan Quick Ratio Terhadap Return On Asset (Studi Kasus Sub Sektor Keramik Porselin Dan Kaca Yang Terdaftar Di Bursa Efek Indonesia) - Masiratul maula (Jurnal Ekonomi dan Bisnis Digital, 2024)
Abstract. This research aims to analyze the influence of the current ratio, Quick Ratio on return on assets in porcelain and glass ceramic companies listed on the Indonesia Stock Exchange (BEI). The data used in this research is secondary data obtained from the financial reports of chemical companies listed on the IDX during the 2020-2023 period. The analytical method used is multiple linear regression. The research results show that the current ratio and Quick Ratio simultaneously have a significant effect on return on assets. Partially, the current ratio and quick ratio have a positive and significant effect on return on assets.